On the toxicity of gold nanoparticles: Histological, histochemical and ultrastructural alterations. (December 2022) - Jarrar, Qais; Al-Doaiss, Amin; Jarrar, Bashir M.; Alshehri, Mohammed
Gold nanoparticles (Au NPs) are used in diagnostic and therapeutic applications together with a variety of industrial purposes and in many biomedical sectors with potential risks to human health. The present study aimed to the histological, histochemical, and ultrastructural alterations induced by Au NPS in vital organs. Healthy male Wistar Albino rats ( Rattus norvegicus ) were subjected to 20 injections of 10-nm Au NPs at a daily dose of 2 mg/kg. Liver, kidney, heart, and lung biopsies from control and Au NPs-treated rats under study were subjected to histological and histochemical examinations. In comparison with the control rats, the renal tissue of Au NPs-treated rats demonstrated glomerular congestion, interstitial inflammatory cell infiltration, renal tubular hydropic degeneration, cloudy swelling, necrosis, and hyaline cast precipitation. In addition, Au NPs induced the following hepatic alterations: hepatocyte cytolysis, cytoplasmic vacuolation, hydropic degeneration, and nuclear alterations together with sinusoidal dilatation. Moreover, the hearts of the treated rats demonstrated myocarditis, cardiac congestion, hyalinosis, cardiomyocyte hydropic degeneration, myofiber disarray and cardiac congestion. The lungs of Au NPs-treated rats also exhibited the following pulmonary alterations: alectasis, emphysema, inflammatory cell inflammation, thickened alveolar walls, pulmonary interstitial edema, congestion, hypersensitivity, fibrocyte proliferation, and honeycombing. In conclusion, exposure to Au NPs induced histological, histochemical and ultrastructural alterations in the vital organs that may alter the function of these organs. Additional efforts are needed for better understanding the potential risks of Au NPs to human health.